Does Crime Lower Growth? : Evidence from Colombia - Cárdenas, Mauricio; Rozo, Sandra (World Bank, Washington, DC, 2017)
Many analysts consider that lack of security is a major obstacle to growth in Colombia. This paper identifies a structural downturn in economic growth-of nearly two percentage points per year-as a result of the increase in illicit crops and crime rates after 1980. A decline in total factor productivity has been the key channel linking crime and economic growth. Political upheavals and high levels of inequality and poverty motivated the adoption of a new constitution in 1991. The constitution mandated additional fiscal expenditures to curb social tensions. Major progress has been made in terms of public safety and, to a lesser extent, in the provision of health and education. However, long?run growth will continue to be constrained by inadequate transport infrastructure and low international trade volumes.